Role of Adipose-to-Muscle Communication in PCB126-induced Metabolic Defects - Caron, Audrey (Université d'Ottawa / University of Ottawa, 2018)
Despite the importance of muscle in the development of type 2 diabetes, few studies have investigated the effect of polychlorinated biphenyls (PCBs) on muscle energy metabolism. Previous results from our lab suggested that PCB126 exposure induced an indirect negative effect on muscle mitochondrial function. Since PCBs are stored in adipose tissue, we hypothesized that PCB126 alters adipokine secretion which in turn affects muscle metabolism. Objectives. Study the adipose-to-muscle communication in PCB126-induced metabolic defects. Methods. Communication between adipocytes and myotubes was reproduced by exposing C2C12 or mouse primary myotubes to the conditioned medium (CM) of 3T3L1 adipocytes exposed to environmentally relevant PCB126 levels. Results. PCB126 significantly increased adipokine secretion and decreased mitochondrial function, glucose uptake and glycolysis in insulin resistant (IR) but not in insulin sensitive 3T3L1. However, exposure of myotubes to CM of IR 3T3L1 only decreased glucose uptake and insulin sensitivity, without altering myotubes glycolysis or mitochondrial function. Conclusion. Our results suggest that the increased adipokine secretion by adipocytes could explain the decreased muscle glucose uptake and insulin sensitivity when exposed to PCB126.
Keywords: Pollutants; Type 2 Diabetes; PCBs; Muscle; Adipose tissue; Adipokines; Metabolism; Mitochondria